The links between food security and seed security and seed security : facts and fiction that guide response - McGrath, S.; Sperling, L. (Informa UK Limited, 2011)
The food price crisis has led to assumptions that food price rises are due to inadequate food production, and that such food insecurity is linked to seed insecurity. Hence, in response to high food prices, seed resources worth hundreds of millions of US dollars are being shipped into vulnerable farming systems across the world. This article examines the evidence for linking food security to seed security, particularly in acute contexts, and shows how the challenges facing security features of availability, access, and utilisation are markedly different when assessing food security and seed security scenarios. The need for sharper thinking about (a) seed security strategy in itself and (b) the causal links between food security and seed security raises questions about supply-side responses which may wrongly identify both the problem and the solution. The article closes by suggesting ways to refine seed security goals which can provide more refined strategies for addressing food security needs.